ANALISIS FAKTOR INTERNAL DAN EKSTERNAL TERHADAP MINAT DAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI MTS BAITUL HIKMAH TEMPUREJO - M. Iqbal Ibrahim Hamdani; Adzkiyak; Siti Nurul Aini (Irfani, 2025)
This study aims to analyze the internal and external factors that influence students' interest and learning outcomes in Social Studies (IPS) class VIII B at MTS Baitul Hikmah Tempurejo. The background of this study is the low participation of students and learning outcomes that have not reached the minimum standard, which indicates the existence of obstacles in the aspects of interest and motivation to learn. This research uses a qualitative approach with phenomenological methods to explore the subjective experiences of students and teachers. Data collection techniques were conducted through observation, in-depth interviews, and documentation. The results show that internal factors such as intrinsic motivation, self-confidence, and perception of the lesson affect students' interest in learning. Meanwhile, external factors such as teacher teaching methods, parental support, and the availability of infrastructure also determine learning success. This research confirms the importance of collaboration between a contextualized pedagogical approach and a supportive learning environment to create more effective social studies learning. The findings provide a practical contribution for teachers and schools in designing learning strategies that can improve students' motivation and overall learning outcomes.